Everyday power dynamics and hierarchies in qualitative research: The role of humour in the field. (October 2022) - Kaaristo, Maarja
Negotiating the relationships influenced by a combination of identity markers during fieldwork is an important aspect of qualitative data co-creation. Based on ethnographic research with the canal boating and enthusiast communities in the UK, this paper focuses on the mundane power dynamics and hierarchies in research situations. The paper discusses the role of humour in negotiating the interpersonal dynamics and argues for the consideration of power (im)balances in the field beyond assumptions of the researcher as definitely the advantaged side. Joking plays an important role and is used by both research participants and researchers to level the researcher–participant hierarchies as well as to reproduce and reaffirm them. This takes place on a conceptual continuum: first, in terms of their relative rigidity, whereby certain norms, opinions or value systems are reinforced; and secondly, flexibility, whereby the notions about norms and preconceived ideas might shift during the research encounter.